Digital Economy and Finance Integration in Contemporary Indonesia - Sugiharto, Bambang; Harkim, Harkim; Rejekia V Simanungkalit; Ilhamsyah Siregar; Maya Andriani (Institute of Computer Science (IOCS), 2024)
The digital economy is one of modern system. That is an aspect of the economy based on the utilization power of high-tech approach. Clearly that is about empowerment of digital information and communication technology. In our contry, the digital economy system is growing very fast along with the increase of large market potential actually. The purpose of this research is to find out how the role of the digital business economy for the development of the modern market economy in Indonesia. The method used is using library research or library study (library research). The results of this study indicate that the presence of digital system presented of quality, such as better of negotiation, business style, and modern markets but the regular markets still needed for people of Indonesia.